50 MOTEXAFIN GADOLINIUM, A REDOX MEDIATOR, INDUCES APOPTOSIS IN CHRONIC LYMPHOCYTIC LEUKEMIA B CELLS AND IS ADDITIVE OR SYNERGISTIC WITH FLUDARABINE. (1st March 2005) - Naumovski, L.; Bone, N.; Sirisawad, M.; Miller, R.; Jelinek, D.; Tschumper, R.; Kay, N. E.
Abstract : Motexafin gadolinium (MGd, Xcytrin) is a tumor-selective redox mediator that oxidizes intracellular reducing metabolites and protein thiols, thereby generating reactive oxygen species (ROS) through a process known as redox cycling. B-cell chronic lymphocytic leukemia (CLL) has elevated levels of the antioxidant ascorbate, and is known to be sensitive to redox stress. Since MGd can generate ROS through oxidation of ascorbate, we reasoned that MGd would be cytotoxic to CLL cells. Mononuclear cells were isolated from the blood of CLL patients (n = 15) characterized by Rai stage, CD38, FISH and immunoglobulin heavy chain variable (IgVH ) mutational status. CLL cells were incubated in vitro over 2-5 days with MGd at concentrations ranging from 0-50 μM. Cytotoxicity was assessed by flow cytometry using drug fluorescence (> 650 nm). MGd-induced cytotoxicity was found to be dose-dependent over a range of 2.5 to 50 μM in cells from 11 of 15 CLL patients. CLL cells from 11/15 patients treated with 50 μM MGd and 4/15 patients treated with 10 μM MGd had cytotoxicity levels at least 2 fold above baseline. MGd uptake was similar in sensitive and resistant CLL cells, implying that mechanisms other than uptake are responsible for the differential responses. CLL cells that were sensitive to MGd treatment showed an increase in caspase-3 activity and cleavage of the caspase substrate PARP was found by immunoblot, suggesting that MGd induced apoptosis. The induction of apoptosis was found to be exclusive of Rai stage, CLL FISH defects, CD38 expression of IgVH mutational status. Cells from 5 CLL patients were studied for drug synergy using seven concentrations of MGd (7.5-50 μM) and the active moiety F-ara-A of fludarabine (0.25-2.0 μM). The cells were treated with each drug individually or both drugs for 48 hours prior to analysis for cytotoxicity. MGd was found to exhibit additive activity (N = 4) or synergistic (N = 1) effects on CLL B cytotoxicity when combined with fludarabine. Thus, our preclinical results reveal that MGd is cytotoxic to CLL cells in vitro through induction of apoptosis. Furthermore, MGd shows additive or synergistic activity when combined with fludarabine. These results support the evaluation of MGd in ongoing CLL clinical trials utilizing this agent alone or in combination with fludarabine.